VISUAL-SPATIAL LEARNING: A CHARACTERISTIC OF GIFTED STUDENTS - Huda Soud Hindal (European Scientific Journal, ESJ, 2014)
This current study investigated an important characteristics of the high achievement of students in middle school ages of 13-15 (n= 560). Thus, visual-Spatial (V/S) was measured using new V/S test. This study aims to establish a new understanding of some of the characteristics of those seen as gifted students as well as to consider some aspects of the ways selection is conducted and needs are met. It was found that those who were very able (in terms of examination performance) tend to be strongly visual-spatial, and of high working memory. It was also found that the assessment of the six school subjects measured the same ability, which is likely to be recall.